MATERIAL POSITION OF JUDGES AND JUDICIAL INDEPENDENCE: AN EXAMPLE OF A DECISION OF THE CONSTITUTIONAL COURT OF SLOVENIA - Damnjanović, Aleksa (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
Material position of the judges is one element of the personal independence of judges. Judicial salaries should be determined in a way they correspond to the dignity and responsibility of judicial profession, but at the same time to protect judges from pressure on decision-making which could jeopardize their independence and impartiality. The first part of the article considers material position of the judges and judicial independence. In the second part is shortly represented material position of judges in Serbian law. The third part of the paper is dedicated to the decision of the Constitutional Court of Slovenia U-I-772/21 of 01.06.2023. in which this court has dealt with this issue, considering it from the perspective of the judicial independence, but also from perspective of the separation of powers.
Keywords: judicial independence; judicial salaries; remuneration; judiciary; judicial organization law; constitutional law